Integrating Chinese cultural philosophies on the effects of employee friendliness, helpfulness and respectfulness on customer satisfaction - Liu, M.; Yan, L.; Phau, Ian; Perez, A.; Teah, Min (Emerald, 2016)
Purpose: This study aims to investigate the main and interactive effects of three employee attributes, namely, employee friendliness, helpfulness and respectfulness, on customer satisfaction in Mainland China. Design/methodology/approach: A 2 × 2 × 2 between-subjects experimental design enabled an eight-scenario study depicting a service experience manipulated by employee friendliness (high/low), helpfulness (high/low) and respectfulness (high/low). Findings It is found that the effect of respectfulness has the strongest impact on customer satisfaction. Customer satisfaction generated by helpfulness is higher when respectfulness is high rather than low, while the interaction between helpfulness and friendliness is not found, even though helpfulness exerts a stronger effect than friendliness on customer satisfaction. Customer satisfaction is also maximized when all three positive interpersonal attributes all jointly presented. Interestingly, the absence of respectfulness tends to trigger a negative effect, while the display of friendliness results in a positive effect.Research limitations/implications: Beyond the joint positive effects on service outcomes, different interaction patterns reveal that the display of friendliness is desirable and beneficial to enhance interpersonal outcome. However, the communication of respect is crucial, and, as such, managers and employees need to strive for a good balance on how to demonstrate these behaviours in critical moments such as service recovery. The findings from relative and interactive effects of three employee attributes are new in the literature and provide significant theoretical and managerial contributions for both researchers and managers. Originality/value: This study takes the first step in decoding the cultural meaning of employee attributes through integrating Chinese traditional philosophy, Li (i.e. politeness), into a specific service setting by examining its comparative effects with other attributes.